Analisis RASIO ROA, ROE, NPM, DER dan LDR Terhadap Harga Saham BNI (BBNI) Pada Tahun 2019-2023 - Nawasari, Nawasari; Sibarani, Mentiana (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the impact ratios on the stock price of BNI (BBNI) during the 2019-2023 period. The ratios examined include Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) as profitability indicators Debt to Equity Ratio (DER) as a solvency indicator and Loan to Deposit Ratio (LDR) as a liquidity indicator. The observed phenomenon is the dynamic interaction between BNI’s fundamental performance and market perception and reaction, especially amidst global and domestic economic volatility, including the COVID-19 pandemic. It is expected that an increase in ROA, ROE, and NPM will positively correlate with an increase in stock price, reflecting the bank’s efficiency and profitability, which are attractive to investors. Conversely, a controlled or decreasing DER and a strong LDR are expected to strengthen investor confidence in BNI’s financial health, thereby supporting stock price stability or appreciation. This study provides empirical evidence that Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Loan to Deposit Ratio (LDR) individually exert a significant influence on the stock price of stock price BNI (BBNI). Conversely, Return On Asset (ROA) and Return On Equity (ROE) were found to have no significant partial effect on BBNI’s stock price during the same period. However, when tested simultaneously, all five vvariabels ROA, ROE, NPM, DER, and LDR collectively demonstrate a significant impact on BBNI’s stock price for the period of 2019-2023.